The Relationship Between Mastery of Nahwu Sharf and The Ability to Translate Arabic Texts - Krisnawilujeng, Karunia; Fatoni, Ahmad; Sarimov, Renat (Arabi : Journal of Arabic Studies, 2023)
In translation, one will face difficulties transferring Arabic texts into Indonesian. There are often many inconsistencies in language change when it has been translated. Nahwu and sharf are often linked to the problem. It is incomplete for someone to learn this nahwu sharf, which makes the Arabic translation imperfect. Likewise with the reality that happened to the 5th semester students Department of Arabic Teaching, University of Muhammadiyah Malang. This study aims to determine the relationship between mastery of nahwu sharf and the ability to translate Arabic texts into Indonesian. The results of the Pearson Correlations Bivariate test on this test with sig (2-tailed) by 5% and    = 0.468, showing a result of 0.574 > 0.468, which means  > . This study shows a significant relationship between the two variables. Based on correlation results = 0.574, it is located at intervals 0.40 – 0.599, which means the relationship between the two variables lies at a medium-level correlation. This answer is that mastery of nahwu sharf is not the only aspect that influences translation skills; various other aspects influence the ability to translate Arabic texts.